Economic development, family wealth and settlement of the personal life and work1 = Desarrollo económico, riqueza familiar y conciliación de la vida personal y laboral - Crespo Garrido, María (Comunitania. Revista Internacional de Trabajo Social y Ciencias Sociales, 2012)
In the last half century, European countries have experienced an increased participation of women in the labor market, what has coincided with a decline in fertility and the emergence of a number of problems related to reconciling of personal and family with a clear female bias. The differences in the time of the use between men and women show that, although the participation of women in paid work has increased, the incorporation of men into the domestic sphere is being too slowly, so that the differences between sexes are important although shortening. En el último medio siglo los países europeos han experimentado un incremento de la participación de las mujeres en el mercado de trabajo, lo que ha coincidido con una caída de la fecundidad y con la aparición de una serie de problemas relacionados con la conciliación de la vida personal y familiar con un claro sesgo femenino. Las diferencias en el empleo del tiempo entre hombres y mujeres ponen de manifiesto que, aunque aumente la participación de las mujeres en el trabajo remunerado, la incorporación del hombre a la esfera doméstica está siendo excesivamente lenta, por lo que las diferencias entre sexos, aunque se van acortando siguen siendo significativas.